The Effectiveness of Weekly Iron Supplementation in Increasing Haemoglobin Level and Preventing Anaemia in Infants - Muhammad Waqas Ashfaq , Saba Naim Khan , Sehrish Mukhtar Cheema,Muhammad Waqqas Akram (Journal of Rawalpindi Medical College, 2015)
Background: To determine the effect of weekly iron supplementation on haemoglobin values and prevention of anaemia compared with control in otherwise healthy infants. Methods: In this randomized controlled study healthy infants between ages 6-12 months were enrolled through consecutive sampling technique and randomized each to one of two study groups; Intervention Group-1 was given 5mg of elemental iron per kilogram of body weight once weekly and control Group-2 received Placebo once weekly. Anthropometric and haematological measurements were performed for both groups before and 12weeks after intervention. Results: Ninety eight infants were included and 76 completed the study with mean age of 9.36months. The average weight and length of infants in both groups increased significantly in the study period with no difference among both the groups. Mean haemoglobin increased significantly in Group-1 from 10.62±1.03g/dl to 11.83±0.76g/dl while the change in haemoglobin concentration was minor in Group-2 from 10.90±1.14g/dl to 11.08±1.11g/dl. Initial values of haematocrit 32.32±2.81%(Group-1), 32.78±2.92%(Group-2) and MCV 65.45±5.12fl(Group-1), 67.13±4.92fl(Group-2) were comparable between the groups, but after treatment haematocrit 36.5±2.37%(Group-1), 33.84±3.20%(Group-2) and MCV 72.45±3.27fl(Group-1), 69.52±4.86fl (Group-2) increased significantly in group 1. Serum Ferritin levels in Group-1 increased from 17.25±26.88ug/L to 53.00±23.69ug/L but it remained unchanged in Group-2 from 13.50±7.49ug/L to 12.55±4.73ug/L. Conclusion: Once-weekly iron supplementation is an effective, cheap, and simple intervention that significantly increases haemoglobin level and improves iron status in infants.